Realistic textures - Cardaci, Diane (Drawing made easy., 2006)
With step-by-step projects that are designed to help sharpen artists' skills and heighten their confidence, this book demonstrates simple techniques for rendering the textures of everyday objects, such as metal, wood, plastic, hair, fur, feathers, and more. This 64-page book simplifies the process with easy-to-understand instructions and comprehensive illustrations.